Dynamics of Business Competition in the Business Sector Online Transportation: Case Study of Grab Indonesia's Discriminatory Allegations Against Independent Drivers According to the Business Competition Supervisory Commission's Perspective - Salsabilasyah, Firyal Nur; Ardhanareswari, Viona; Aulia, Saffira; Tarina, Dwi Desy Yayi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research discusses the dynamics of business competition in the online transportation sector, focusing on a case study of allegations of discrimination by Grab Indonesia against independent drivers. Ride-hailing has become an integral part of modern society, leveraging technological developments to provide efficient and transparent transportation services. However, behind the convenience offered, the issue of unfair business competition arises, such as what happened to Grab Indonesia. This research explores how the cooperation between Grab Indonesia and PT TPI, which provides rental vehicles for drivers, has led to allegations of discrimination against independent drivers. Using a normative juridical research method, this study analyzes the mechanism for resolving violations of law related to discrimination by the Business Competition Supervisory Commission (KPPU). The results show that the discriminatory actions taken by Grab Indonesia have negatively impacted independent drivers and triggered regulatory intervention by KPPU.